Complement component C1q as potential diagnostic but not predictive marker of preeclampsia. (26th September 2016) - Agostinis, Chiara; Stampalija, Tamara; Tannetta, Dionne; Loganes, Claudia; Vecchi Brumatti, Liza; De Seta, Francesco; Celeghini, Claudio; Radillo, Oriano; Sargent, Ian; Tedesco, Francesco; Bulla, Roberta
Abstract : Problem: We have previously found that C1q is constitutively expressed by invading trophoblast and endothelial cells of decidua and contributes to vascular and tissue remodeling. Based on these findings, we sought to determine whether there were changes in the circulating level of C1q that may be used as a diagnostic and predictive marker of preeclampsia. Method of Study: We measured the levels of C1q, C4, and complement activation products in serum or plasma of normal pregnant women and preeclamptic patients from different cohorts. Results: We observed a marked decrease in the concentration of C1q associated with a reduced level of C4 in preeclamptic patients as compared to matched healthy pregnant woman but no significant difference in the circulating level of the activating products C5a and the soluble terminal complement complex sC5b‐9. Analysis of serum samples collected at early phase of pregnancy from women who later developed preeclampsia failed to show a decrease in C1q level. Conclusion: The results of the present investigation demonstrate that low levels of C1q and C4 are associated with preeclampsia but cannot be used as predictive markers.